PENYULUHAN KIAT UNTUK MEMULAI USAHA BARU KEPADA PENGURUS BADAN KESWADAYAAN MASYARAKAT (BKM) DAMAI SEJAHTERA - Mislan Sihite; Rasmulia Sembiring; Robinhot Gultom; Sahat Parulian Remus Silalahi; Siti Normi; Saur Melianna; Tiur Rajagukguk; Winarto Winarto; Sondang Ni Bulan Marbun; Rommel Sitohang; Selamat Siregar; Toman Panggabean (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service is one of the Tri Dharma of Higher Education and this activity is very beneficial to the community and to the lecturers who carry out these activities. The Lecturers of the Faculty of Economics, Management Study Program carried out this activity at the Damai Prosperous Community Self-Reliance Agency (BKM) in Sukaraja Village - Medan Maimun District with the topic "Tips for Starting a New Business". The method used is lectures and guided discussions. The conclusions that can be formulated are the need to know the reasons for having a business, what to think about when opening a business, types of business fields that have prospects in the future, various successful strategies for starting a business venture, high enthusiasm is needed to become an entrepreneur, and practical matters in starting a business, as well as what competencies an entrepreneur/entrepreneur must have